The acute effects of different training loads of whole body vibration on flexibility and explosive strength of lower limbs in divers - G Dallas; G Paradisis; P Kirialanis; V Mellos; P Argitaki; A Smirniotou (Termedia Publishing House, 2015)
The purpose of this study was to examine the acute effects of different vibration loads (frequency and amplitude) of whole-body vibration (WBV) on flexibility and explosive strength of lower limbs in springboard divers. Eighteen male and female divers, aged 19 ± 2 years, volunteered to perform 3 different WBV protocols in the present study. To assess the vibration effect, flexibility and explosive strength of lower limbs were measured before (Pre), immediately after (Post 1) and 15 min after the end of vibration exposure (Post 15). Three protocols with different frequencies and amplitudes were used in the present study: a) low vibration frequency and amplitude (30 Hz/2 mm); b) high vibration frequency and amplitude (50 Hz/4 mm); c) a control protocol (no vibration). WBV protocols were performed on a Power Plate platform, whereas the no vibration divers performed the same protocol but with the vibration platform turned off. A two-way ANOVA 3 x 3 (protocol × time) with repeated measures on both factors was used. The level of significance was set at p < 0.05. Univariate analyses with simple contrasts across time were selected as post hoc tests. Intraclass coefficients (ICC) were used to assess the reliability across time. The results indicated that flexibility and explosive strength of lower limbs were significantly higher in both WBV protocols compared to the no vibration group (NVG). The greatest improvement in flexibility and explosive strength, which occurred immediately after vibration treatment, was maintained 15 min later in both WBV protocols, whereas NVG revealed a significant decrease 15 min later, in all examined strength parameters. In conclusion, a bout of WBV significantly increased flexibility and explosive strength in competitive divers compared with the NVG. Therefore, it is recommended to incorporate WBV as a method to increase flexibility and vertical jump height